A test for Y‐linked additive and epistatic effects on surviving bacterial infections in Drosophila melanogaster. (14th June 2017) - Kutch, I. C.; Fedorka, K. M.
Abstract: Y‐ and W‐chromosomes offer a theoretically powerful way for sexual dimorphism to evolve. Consistent with this possibility, Drosophila melanogaster Y‐chromosomes can influence gene regulation throughout the genome; particularly immune‐related genes. In order for Y‐linked regulatory variation (YRV) to contribute to adaptive evolution it must be comprised of additive genetic variance, such that variable Ys induce consistent phenotypic effects within the local gene pool. We assessed the potential for Y‐chromosomes to adaptively shape gram‐negative and gram‐positive bacterial defence by introgressing Ys across multiple genetic haplotypes from the same population. We found no Y‐linked additive effects on immune phenotypes, suggesting a restricted role for the Y to facilitate dimorphic evolution. We did find, however, a large magnitude Y by background interaction that induced rank order reversals of Y‐effects across the backgrounds (i.e. sign epistasis). Thus, Y‐chromosome effects appeared consistent within backgrounds, but highly variable among backgrounds. This large sign epistatic effect could constrain monomorphic selection in both sexes, considering that autosomal alleles under selection must spend half of their time in a male background where relative fitness values are altered. If the pattern described here is consistent for other traits or within other XY (or ZW) systems, then YRV may represent a universal constraint to autosomal trait evolution.